2022
DOI: 10.3389/fsurg.2022.915052
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Trajectory for a Transpedicular Approach in the Treatment of a Highly Downward-Migrated Lumbar Herniation with a Full Endoscopic Technique

Abstract: BackgroundTo evaluate the clinical outcome of full endoscopic discectomy using a novel trajectory via a transpedicular approach.MethodThirty-five patients were enrolled in this retrospective study between July 2014 and October 2019 in the Beijing Haidian Hospital. All patients were treated with full-endoscopic lumbar discectomy via a transpedicular approach with an oblique trajectory. The imaging parameters, including pedicle height and angle of trajectory, were recorded. The preoperative and postoperative cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The endoscopic transpedicular approach is a valuable option in case in of high-grade downmigrated lumbar disc herniations 13–15 . Until now, its biomechanical consequence was unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The endoscopic transpedicular approach is a valuable option in case in of high-grade downmigrated lumbar disc herniations 13–15 . Until now, its biomechanical consequence was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Krzok et al 11,12 first described the transpedicular approach to accessing highly downmigrated disc herniations, followed by a limited number of case studies with reported good clinical outcome 13,14,29 . Jiang et al 15 included 35 patients in a retroperspective study showing good clinical results and confirmed bony healing of the transpedicular hole with a CT scan six months postoperatively for all patients. None of the abovementioned publications 11–15,29 described severe complications, including a pedicle fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous transforaminal endoscopic lumbar discectomy (TELD) is a minimally invasive surgical procedure performed while the patient is awake through an incision of no more than 1 cm in length. Compared with traditional open surgery, TELD is preferred due to the advantages of less pain, less paravertebral muscle injury, preservation of the posterior ligamentous, and faster recovery (1)(2)(3). Despite the remarkable evolution of endoscopic techniques and instrumentation, traditional TELD requires extensive training for surgeons to overcome its steep learning curve (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the rapid development of this technology is that, compared with traditional open spine surgery, FESS does not involve massive destruction of muscle tissue, there is no need for the destruction of synovial joints and vertebral plates, and it lessens the distraction of nerve roots and dural sacs which ensures maximum stability of the spinal segment and reduces the occurrence of long-term pain and discomfort due to spinal instability and other complications (5)(6)(7). After decades of development, the use of FESS has gradually expanded from simple lumbar disc herniation (DH) to lumbar spinal stenosis and instability treatment; from lumbar to cervical and thoracic spine treatment; from pure decompression to endoscopicassisted fusion techniques; and from the treatment of degenerative spine diseases to that of spinal trauma, infection, deformity, and tumors (8)(9)(10)(11). With the widespread popularity of FESS, the amount of research in this field is increasing.…”
Section: Introductionmentioning
confidence: 99%